Remote Cerebellar Hemorrhage after Revision Lumbar Spine Surgery. (December 2015) - Haller, Justin M.; Calvert, Graham; Spiker, William R.; Brodke, Darrel S.; Lawrence, Brandon D.
Study Design: Case report. Objective: To report a case of remote cerebellar hemorrhage (RCH) without intraoperative dural tear after revision lumbar spine surgery. RCH is a rare postoperative complication following spine surgery. RCH has previously been reported only in cases with intraoperative dural tear or durotomy. Methods: Case report and literature review. Results: A 58-year-old woman underwent removal of L4–S1 posterior spinal instrumented fusion (PSIF) implants and L3–L4 decompressive laminectomy with PSIF. There was no intraoperative dural tear. After doing well initially, the patient developed new neurologic symptoms and was found to have RCH. Lumbar spine magnetic resonance imaging (MRI) demonstrated a large dural defect. After repair of the dura, the patient had dramatic improvement of her neurologic symptoms. At 1-year follow-up, the patient continued to have no neurologic sequelae. Conclusion: This report demonstrates that RCH can occur without intraoperative dural tear. Although rare, any patient with new onset of declining neurologic symptoms following spine surgery should have a brain MRI and should have RCH on the differential diagnosis.